Three remarkable Byzantine lead seals from a private collection - CHARALAMPAKIS, Pantelis (Byzantina Symmeikta, 2023)
This study focuses on the publication of - and commentary on - three Byzantine lead seals that are part of a larger registered private collection. The first two are remarkable because of their owners' names, rarely attested in Late Antiquity and the Middle Byzantine period: Βιάτωρ / Viator (droungarios, date: ca. 650-700) and Genethlios (stratelates, date: ca. 750-825). The third, which belonged to a certain Ioannes, taboullarios (date: ca. 650-725), demonstrates a mixture of Greek and Latin symbols in a Greek inscription and, perhaps, is among the latest of this kind.